2016
DOI: 10.1177/0895904816637689
|View full text |Cite
|
Sign up to set email alerts
|

The Role of School Context in Implementing a Statewide Anti-Bullying Policy and Protecting Students

Abstract: Bullying is a significant problem in U.S. schools. Policies have been developed to reduce bullying, yet policy implementation by educators is an essential yet difficult and complex process. Few studies have investigated factors that act as barriers to or facilitators of bullying policy implementation and teacher protection of students. This study examined the influence of school context on educators’ capacity to implement a statewide bullying law and protect students from bullying following the enactment of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 96 publications
1
33
0
Order By: Relevance
“…The implementation of a policy is a complex, dynamic, and ongoing process involving a vast assortment of people, resources, organizational structures, and actions. No study that examined the implementation of school bullying policies found that the policies were being implemented precisely as intended (Hall & Chapman, 2016a, 2016b; Hedwall, 2006; Holmgreen, 2014; Jordan, 2014; LaRocco, Nestler-Rusack, & Freiberg, 2007; MacLeod, 2007; Robbins, 2011; Schlenoff, 2014; Smith-Canty, 2010; Terry, 2010). Indeed, the extent of faithful implementation in these studies varied considerably by location and policy component.…”
Section: Discussionmentioning
confidence: 99%
“…The implementation of a policy is a complex, dynamic, and ongoing process involving a vast assortment of people, resources, organizational structures, and actions. No study that examined the implementation of school bullying policies found that the policies were being implemented precisely as intended (Hall & Chapman, 2016a, 2016b; Hedwall, 2006; Holmgreen, 2014; Jordan, 2014; LaRocco, Nestler-Rusack, & Freiberg, 2007; MacLeod, 2007; Robbins, 2011; Schlenoff, 2014; Smith-Canty, 2010; Terry, 2010). Indeed, the extent of faithful implementation in these studies varied considerably by location and policy component.…”
Section: Discussionmentioning
confidence: 99%
“…Studies show that the frequency of aggression among students increases the need for training and qualification of teachers, other pedagogical coordinators, and school administrators to deal effectively with the problem. Where protection has been tried, including better teacher training, there has been a reduction of perceived maltreatment among students as well as better perceived social coherence at school …”
Section: Discussionmentioning
confidence: 99%
“…Where protection has been tried, including better teacher training, there has been a reduction of perceived maltreatment among students as well as better perceived social coherence at school. 1,32,33 Regarding help of a school professional, only 2 apps met this feature (Feature 5, Table 2). Research brings primary attention to combating violence in schools by greater involvement and responsiveness of teachers, school psychologists, administrators and other school personnel who are inserted in the school environment.…”
Section: Discussionmentioning
confidence: 99%
“…With "systemic omission" of LGBT concerns in educator preparation programs (Gorski et al 2013, p. 230) and no clear policies and guidance in place, personal biases may be foregrounded in an educator's response to a LGBT student. Many educators remain resistant to openly addressing LGBT issues, and research confirms a prevalence of negative attitudes toward LGBT people among both pre-service and licensed teachers (Hall and Chapman 2018;Macgillivray and Jennings 2008). One study found that school sexual harassment policy did little to disrupt the targeting of gay and lesbian students because the policy did not provide specific guidance for responding to LGBT gender-based bullying and, ultimately, educators' individual biases and beliefs about gendered relations shaped how they interpreted gender-based aggression between students (Anagnostopoulos et al 2009).…”
Section: Need For Lgbt-specific Policymentioning
confidence: 99%